How Fear Appeal Approaches in COVID-19 Health Communication May Be Harming the Global Community. (August 2020) - Stolow, Jeni A.; Moses, Lina M.; Lederer, Alyssa M.; Carter, Rebecca
As health professionals develop health communication for coronavirus disease 2019 (COVID-19), we implore that these communication approaches do not include fear appeals. Fear appeals, also known as scare tactics, have been widely used to promote recommended preventive behaviors. We contend that unintended negative outcomes can result from fear appeals that intensify the already complex pandemic and efforts to contain it. We encourage public health professionals to reevaluate their desire to use fear appeals in COVID-19 health communication and recommend that evidence-based health communication be utilized to address the needs of a specific community, help people understand what they are being asked to do, explain step-by-step how to complete preventative behaviors, and consider external factors needed to support the uptake of behaviors. To aid health professionals in redirecting away from the use of fear appeals, we offer a phased approach to creating health communication messages during the COVID-19 crisis.